Oxygen and potassium vacancies in KTP calculated from first principles - Bocchini, Adriana; Neufeld, Sergej; Gerstmann, Uwe; Schmidt, Wolf Gero (Journal of Physics: Condensed Matter)

LiNbO3 surfaces from a microscopic perspective - Sanna, Simone; Schmidt, Wolf Gero (Journal of Physics: Condensed Matter)

Advanced capabilities for materials modelling with Quantum ESPRESSO - Giannozzi, P; Andreussi, O; Brumme, T; Bunau, O; Buongiorno Nardelli, M; Calandra, M; Car, R; Cavazzoni, C; Ceresoli, D; Cococcioni, M; Colonna, N; Carnimeo, I; et al. (Journal of Physics: Condensed Matter)

Curvature effects in the band structure of carbon nanotubes including spin–orbit coupling - Liu, Hong; Heinze, Dirk Florian; Thanh Duc, Huynh; Schumacher, Stefan; Meier, Torsten (Journal of Physics: Condensed Matter)

Curvature effects in the band structure of carbon nanotubes including spin–orbit coupling - Liu, Hong; Heinze, Dirk Florian; Thanh Duc, Huynh; Schumacher, Stefan; Meier, Torsten (Journal of Physics: Condensed Matter)
The Kane–Mele model was previously used to describe effective spin–orbit couplings (SOCs) in graphene. Here we extend this model and also incorporate curvature effects to analyze the combined influence of SOC and curvature on the band structure of carbon nanotubes (CNTs). The extended model then reproduces the chirality-dependent asymmetric electron-hole splitting for semiconducting CNTs and in the band structure for metallic CNTs shows an opening of the band gap and a change of the Fermi wave vector with spin. For chiral semiconducting CNTs with large chiral angle we show that the spin-splitting configuration of bands near the Fermi energy depends on the value of $\text{mod}(2n+m,3)$ .

The atomic structure of ternary amorphous TixSi1−xO2hybrid oxides - Landmann, M; Köhler, T; Rauls, E; Frauenheim, T; Schmidt, Wolf Gero (Journal of Physics: Condensed Matter)

The effect of (NH4)2Sxpassivation on the (311)A GaAs surface and its use in AlGaAs/GaAs heterostructure devices - Carrad, D J; Burke, A M; Reece, P J; Lyttleton, R W; Waddington, D E J; Rai, A; Reuter, Dirk; Wieck, A D; Micolich, A P (Journal of Physics: Condensed Matter)

Elemental distribution, solute solubility and defect free volume in nanocrystalline restricted-equilibrium Cu–Ag alloys - Riedl, Thomas; Kirchner, A; Eymann, K; Shariq, A; Schlesiger, R; Schmitz, G; Ruhnow, M; Kieback, B (Journal of Physics: Condensed Matter)
In this article we study the elemental distribution and solute solubility in nanocrystalline alloys of immiscible components near restricted equilibrium for the case of the binary Cu–Ag system. As predicted from thermodynamic considerations, a grain boundary segregated monophase alloy is observed in the annealed mechanically alloyed state for low Ag content by using atom probe tomography. From the detected Ag solute grain boundary enrichment the segregation free enthalpy is estimated to range between -25 and -49 kJ mol^-1 following the McLean equation, in agreement with values reported for coarse-grained Cu–Ag. The extension of the alloying range is described by a two-domain thermodynamic model that considers the excess free volume in the grain boundaries and the strain in the strain interior on the basis of the universal equation of state at negative pressure. To access the grain boundary volumetric strain experimentally, a method based on a combination of density measurements and microscopical quantification of closed pore areas is presented. Moreover, we apply x-ray diffraction line broadening analysis to determine the local strain amplitude, which yields a root-mean-square microstrain of 0.3% for a grain size of 30 nm. It is shown that the grain boundary free volume represents the major origin for the global solubility enhancement in nanocrystalline Cu–Ag at 503 K.

Photoluminescence lineshape features of carbon δ-doped GaAs heterostructures - Schuster, J; Kim, T Y; Batke, E; Reuter, Dirk; Wieck, A D (Journal of Physics: Condensed Matter)

The electronic structure and optical response of rutile, anatase and brookite TiO2 - Landmann, M; Rauls, E; Schmidt, Wolf Gero (Journal of Physics: Condensed Matter)